2020
DOI: 10.1016/j.ress.2019.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of digitalization of nuclear power plant control rooms on human reliability analysis – A review

Abstract: The changes in the operating conditions of the main control room of nuclear power plants due to new digitalized human-system interfaces (HSIs) pose challenges to traditional human reliability analysis (HRA) methods. This paper reviews current knowledge about the effect of digital HSI on human behaviour and reliability, relevant performance shaping factor (PSF) taxonomies as well as research on the effect of PSFs on human error probability estimates in advanced control rooms (ACRs). It cannot be generally concl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 40 publications
(80 reference statements)
0
16
0
Order By: Relevance
“…Other evaluation approaches include human-in-the-loop evaluation [163], balancing principles [164], augmented reality-based evaluation [165], and so on. While research shows that control room digitalization including HMI, which we deem as a significant improvement to NPP, has both positive and negative effects on the reliability of human operators [166], depending on the detailed design. The main problems with this are increased complexity for the system and workload…”
Section: ) Human-machine Interactionmentioning
confidence: 96%
See 1 more Smart Citation
“…Other evaluation approaches include human-in-the-loop evaluation [163], balancing principles [164], augmented reality-based evaluation [165], and so on. While research shows that control room digitalization including HMI, which we deem as a significant improvement to NPP, has both positive and negative effects on the reliability of human operators [166], depending on the detailed design. The main problems with this are increased complexity for the system and workload…”
Section: ) Human-machine Interactionmentioning
confidence: 96%
“…Some of the limitations of these capabilities cannot be overcome by mental work, but need to be supported by appropriate user interface quality. In recent years, NPPs have gradually become digital, but the design of digital solutions cannot simplify the work of operators [64]. Zhang et al [65] found that although the digital user interface has greatly changed the way operators access, store, process, and output information, it does not consider more emotional aspects such as stress and workload.…”
Section: A Current Limitations In Nppsmentioning
confidence: 99%
“…Unsafe actions by construction personnel not only directly lead to accidents, but can also indirectly trigger incidents by altering the state of objects [8]. The introduction of additional interface management tasks for crane operators increases cognitive and operational loads, elevating the potential for human errors such as mode confusion and loss of situational awareness [9]. As a result, the reliability and safety of human-machine interaction systems for cranes with visual hooks increasingly depend on human factors [10].…”
Section: Introductionmentioning
confidence: 99%
“…These team coordination processes involve both information transmission and behavior interaction among crew members (Fisher, 2014; Kolbe et al, 2013), and thus require intensive time and effort of the whole team. With the digitalization of the NPP control room, operators have to concentrate on massive changing parameters of the nuclear system, as well as the progress and status of the emergency task and the team activity of coworkers (Jung & Park, 2020; Lee & Cha, 2019; Porthin et al, 2020). This emerging digital trend has added more difficulty to the team coordination of control crews than ever before.…”
Section: Introductionmentioning
confidence: 99%